Risk Factors of Hypertension among Adult in Rural Indonesia - Diana, Rian; Muharam Nurdin, Naufal; Anwar, Faisal; Riyadi, Hadi; Khomsan, Ali (The Food and Nutrition Society of Indonesia in collaboration with the Department of Community Nutrition, IPB University, 2018)
The aim of this study was to analyse the risk factors of hypertension among adult in rural Indonesia. This cross-sectional study included 112 married couples (112 men and 112 women) aged 45-59 years old and was conducted in Cianjur District, West Java, Indonesia. The measurement of body weight and fat composition used Bioelectrical Impedance Analysis (BIA) monitor (OMRON® Karada Scan Body Composition Monitor HBF-358-BW). Body height was measured by stadiometer, meanwhile waist circumference was measured by measuring tape. Data on the blood pressure measured by an automatic blood pressure monitor (OMRON® Automatic Blood Pressure Monitor Model HEM-7200). All measurement were done twice in repetition. Chi-square was used to analysed the association between variables and logistic regression was used to analyse the risk factors. The prevalence of hypertension was 49.1% (women 54.5%; men 43.7%). Women had a higher proportion of overweight, obesity, abdominal obesity, and hypertension stage 2 than men. BMI (p<0.05), waist circumference (p<0.05), total body fat (p<0.05), and visceral fat (p<0.05) were significantly higher in hypertension subject than not hypertension. Nonetheless, only waist circumference became the risk factor for hypertension (OR=4.005; 95%CI:1.47-10.914 for high risk). There is high prevalence of hypertension among adult in rural area. Adult, particularly women need to pay attention on their body fat to reduce the risk of hypertension.